Physicians' recognition of death in the foreseeable future in patients with intellectual disabilities. Issue 3 (12th January 2016) - Vrijmoeth, C.; Christians, M. G. M.; Festen, D. A. M.; Groot, M.; Tonino, M.; Echteld, M. A.
Abstract: Background: Physicians are increasingly confronted with people with intellectual disabilities (ID) who are facing life‐threatening diseases. We aimed to explore when and based on which information sources and signals physicians recognised that a patient with ID would die in the foreseeable future. Insights may help in identifying patients in need of palliative care. Method: In this study, 81 physicians for people with ID and 16 general practitioners completed a retrospective survey about their last case of a patient with ID with a non‐sudden death. Results: More than 20% of all physicians foresaw death not until the last week of life. In 30% of all patients, the physician did not discuss the start of the palliative care phase until the last week. The most reported information sources based on which physicians foresaw death were the physicians themselves and professional caregivers. We found 40 different signals that lead to physicians' foreseeing death. These were not only medical signals but also behavioural and physical signals. Conclusions: Results indicate that the physicians' ability to foresee death is a result of a process of growing awareness in which multiple signals from different information sources converge. This demands continuous multi‐disciplinary communication because people involved have their own unique interactions with the patient and can therefore contribute to a growing and timely awareness of patients' death in the future.